A randomized, double-blinded, double-dummy efficacy and safety study of budesonide–formoterol Spiromax® compared to budesonide–formoterol Turbuhaler® in adults and adolescents with persistent asthma. Issue 1 (December 2016) - Virchow, J.; Rodriguez-Roisin, Roberto; Papi, Alberto; Shah, Tushar; Gopalan, Gokul
Abstract Background Budesonide and formoterol (BF) Spiromax® is a dry powder inhaler designed to deliver BF with maximum ease of use for patients with asthma or chronic obstructive pulmonary disease. Methods A phase 3b, 12-week, multicenter, double-blind, double-dummy, randomized, controlled trial in patients (≥12 years) with persistent asthma. Primary objective: to demonstrate non-inferiority of twice-daily BF Spiromax 160/4.5 mcg to BF Turbuhaler® 200/6 mcg in change from baseline in weekly average of daily trough morning peak expiratory flow (PEF). Secondary endpoints included: Patient Satisfaction and Preference Questionnaire scores, change from baseline in evening PEF, trough forced expiratory volume in one second, percentage of symptom-free and rescue-free 24-hour periods, and safety. Results The analysis was based on the per-protocol population (BF Spiromax, n  = 290; BF Turbuhaler, n  = 284). The least squares mean change from baseline to week 12 in morning PEF was: BF Spiromax, 18.8 L/min and BF Turbuhaler, 21.8 L/min. Non-inferiority of BF Spiromax vs BF Turbuhaler was demonstrated (the lower limit of the 95 % two-sided confidence interval was −9.02 L/min, which is greater than −15 L/min [the criteria specified for non-inferiority]). The mean difference in the total performance domains scores for BF Spiromax vs BF Turbuhaler were 0.248 at baseline and 0.353 at week 12 (both, p <0.001), indicating statistical superiority for BF Spiromax. No statistical or numerical differences were recorded in the total convenience domain score between the two devices. Scores for 'device preference' and 'willingness to continue' supported BF Spiromax at baseline and at week 12 (p  = 0.0005 vs BF Turbuhaler). No significant between-group differences were observed in the other secondary efficacy endpoints. Both treatments were well tolerated, with no significant differences in adverse events or asthma exacerbations. Conclusions This study demonstrates the non-inferiority of BF Spiromax vs BF Turbuhaler in patients (≥12 years) with asthma. More patients preferred the Spiromax device over Turbuhaler for its performance, and were willing to continue therapy with BF Spiromax beyond the 12-week study period. Trial registration NCT01803555 ; February 28, 2013.